Mejan Tanpa Kepala di Kabupaten Pakpak Bharat (Pendekatan Motivasi Religi terhadap Fenomena Pencurian Artefak Megalitik) - Defri Elias Simatupang (Berkala Arkeologi Sangkhakala, 2010)
AbstractThis article studies the problems about phenomenon to the number of mejans (megalitik statue) that founded without head in Regency of Pakpak Bharat, North Sumatera. Through by approach the religion motivation theory, this article try to study those problems pursuant to any kind motivation of existing in the thieves’ mind, which made them dare to steal mystique mejan. The motivations indicated have a link with religion motivation. There are some interesting things found that some of theft case lead mejan. At the end of this article, author want to open anopinion discourse, how to save that mejans so that more taken care and can reduced the risk of stealing mejans.